Clinical profile and Outcome of Enteric Fever in hospitalized children aged 6 months to 2 years (Northern International Medical College Journal, 2015)
Background : Enteric fever is a common endemic disease in Bangladesh.1 Enteric fever caused by Salmonella typhi (typhoid fever) is a major therapeutic consideration of all prolonged illnesses with pyrexia in pediatric practices particularly in developing countries like Bangladesh.Objectives :To evaluate the clinical profile and outcome of enteric fever in hospitalized children aged 6 months to 2 years.Methods: This was a prospective study conducted in the paediatric medicine unit of Dhaka Shishu Hospital during the period of November 2003 to August 2004. Forty children (age 6 months to 2 years) with specific criteria for diagnosing enteric fever enrolled in this study. Statistical analysis were done using the SPSS. All the data were expressed in percentage, mean or standard deviation.Anova test was used as the test for significance.Results : The clinical features, laboratory data, response to treatment were studied in 40 cases of enteric fever(daignosed by prefixed criteria). Majority of the patients belonged to the age group between 9 months to 2 years. Fever was the main presenting feature in all the cases (100%).Other associated features were anorexia (95%), vomiting(85%), diarrhea (80%), abdominal distension(75%), cough (70%), pallor (70%) and lethargy (50%). Of the signs, high temperature 101OF (95%), coated tongue (92.5%), tachycardia (90%), toxic appearance (87.5%) and anemia (70%) were the commonest features while hepatomegaly was present in 37.5% of cases. Typhoid fever was the most frequent (82.5%) enteric fever and the Widal test was significantly positive in 100% of cases. Blood culture was positive in 4 cases only with S. typhi in 3 cases (75%) and S. paratyphi A in 1 case (25%) and all isolated organisms were sensitive to Ceftriaxone and Ciprofloxacin. The outcome of the study population was assessed in terms of improved, cured, failure of treatment, complications and relapse. Cure rate was high (82.5%) in the study group. In the remaining 17.5%, the patients were considered improved. No case of relapse was recorded during the follow-up period of these patients. Failure of improvement or deterioration of clinical condition after treatment was not noted in this study. Complications were minimal in the study population and none of the patients died in this study.Conclusion: Contrary to the popular belief and west-oriented teaching, typhoid is certainly common in infants and young children in countries of the Third World and younger children are more likely to present with a non-specific febrile illness which makes the diagnosis difficult and as such adequate knowledge of the clinical presentations of this age group is essential for effective diagnosis and treatment.Northern International Medical College Journal Vol.5(1) 2013: 301-305